THE TURN ON EAST CAPITAL MARKET: PROSPECTS FOR RUSSIAN ISSUERS - Elena Gunina; Anait Avagyan; Polina Gerasimenko (Вестник Северо-Кавказского федерального университета)
Actual problems of turning on the East capital market for Russian companies, in connection with West sanctions, are reviewed in this article. Main obstacles, which are standing for our issuers on Hong Kong and Singapore stock exchanges, are studied. Also, we have revealed how much Russian companies are interested in East markets.